Harmonisasi Metode Analisis Pengujian Cemaran 1,4-Dioksan dalam Kosmetik sebagai Upaya Memperkuat Pengawasan Pre-Market Melalui Jejaring Laboratorium Kosmetik di Indonesia - Arpan, Susan Gracia; Sri Purwaningsih; Hasti Kusuma; Lusianti, Erita; Yustina, Yustina (Badan Pengawas Obat dan Makanan, 2024)
Laboratories play a strategic role in protecting public health by ensuring the quality and safety of drugs, food, and cosmetics. The Centre of National Quality Laboratory of Drugs and Food (CNQLDF), as the central laboratory of the Indonesian Food and Drug Authority (Indonesian FDA), continuously develops reliable, selective, sensitive, and accurate analytical methods (AM) for cosmetic testing in line with advancements in cosmetic formulation technology. However, both the Indonesian FDA and external cosmetic laboratories need more human resources and infrastructure, hindering the development of analytical method and the testing of cosmetic products. Strengthening these laboratories through stakeholder networks is essential. Indonesia actively participates in the ASEAN Cosmetic Testing Laboratories Committee (ACTLC) and the Indonesian Cosmetic Laboratory Network (ICLN). One of the main tasks of CNQLDF is to develop a new ASEAN Cosmetic Method (ACM) for 1,4-Dioxane contaminants in cosmetics. Currently, CNQLDF, along with the Indonesia National Standard Body (INSB), Ministries and External Laboratories, in which together became members of ICLN, harmonized the analytical method of 1,4-Dioxane at the national level, leading to the issuance of the Indonesian National Standard (INS). Both the INS and ACM have main purpose to standardize analytical methods across laboratories, ensure the safety and quality of cosmetic products and enhance national product competitiveness. This study examines method to strengthen pre-market cosmetic surveillance through harmonizing the analytical method of 1,4-Dioxane at the national and ASEAN regional levels, using a qualitative approach based on the Indonesian FDA's internal data and stakeholder information on 1,4-Dioxane testing capabilities.